2023
DOI: 10.1108/lodj-07-2021-0361
|View full text |Cite
|
Sign up to set email alerts
|

Leader green behavior as an outcome of followers' critical thinking and active engagement: the moderating role of pro-environmental behavior

Abstract: PurposeThe purpose of this study is to investigate the role of followership dimensions of active engagement (AE) and independent critical thinking (ICT) in leader green behavior (LGB), and how followers' pro-environmental behavior (FPEB) moderates between the proposed relationship.Design/methodology/approachThe data was collected from 381 employees working in different small and medium enterprises (SMEs) of Pakistan, through a structured questionnaire with five points Likert scale. The proposed hypotheses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Our literature search (Table 1) identified only one study that is somewhat consistent with this proposition (but did not test potential mechanisms). Specifically, Javaid et al (2023) found that follower active engagement and critical thinking were positively related to leader green behavior.…”
Section: Integrative Conceptual Model Of Leadership and Environmental...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature search (Table 1) identified only one study that is somewhat consistent with this proposition (but did not test potential mechanisms). Specifically, Javaid et al (2023) found that follower active engagement and critical thinking were positively related to leader green behavior.…”
Section: Integrative Conceptual Model Of Leadership and Environmental...mentioning
confidence: 99%
“…Additional individual antecedents examined in the literature include personal values (Egri & Herman, 2000), personality traits like conscientiousness and moral reflectiveness (Kim et al, 2017), and environmental knowledge (Fryxell & Lo, 2003). Only one study showed that follower characteristics (i.e., active engagement and critical thinking) were positively related to leader green behavior (Javaid et al, 2023). Finally, several studies examined contextual antecedents of green leadership.…”
Section: Antecedents Of Green Leadershipmentioning
confidence: 99%
“…Green leadership encourages organizations to generate and share knowledge about sustainable practices, such as green technology, waste management, and renewable energy (Javaid et al, 2023). Green leadership provides opportunities for staff to contribute through platforms, training, and internal meetings.…”
Section: The Relationship Between Variablesmentioning
confidence: 99%
“…The productivity of staff members who are encouraged to adopt organizational citizenship behavior and improve their green behavior for sustainability is higher (Huang, Liu, & He, 2023). On the other hand, putting less emphasis on employee behavior makes it harder for the company to adopt green behavior (Javaid, Kumari, Khan, Jaaron, & Shaikh, 2023). While a company can establish and sustain a culture of sustainability over time, this relies on each employee's willingness to engage in environmentally friendly organizational practices (García-Salirrosas & Rondon-Eusebio, 2022;Sharma, Aswal, & Paul, 2023).…”
Section: Employee Eco-friendly Behaviormentioning
confidence: 99%